Brolucizumab for Neovascular Age-Related Macular Degeneration in Real-World Setting - Nadhira, Andi Marsa; Djatikusumo, Ari; Victor, Andi Arus (Indonesian Vitreoretinal Society, 2023)
Introduction: The mainstay treatment for neovascular AMD (nAMD) is intravitreal injections of anti-vascular growth factor (anti-VEGF) agents. Based on clinical trials, a newly developed anti-VEGF named brolucizumab showed noninferiority in anatomical and functional outcomes with longer injection interval, when compared to previous anti-VEGF agents; however, severe post-injection inflammation has been observed. This review aims to evaluate the efficacy and safety of brolucizumab in real-world clinical setting. Methods: We conducted systematic searches in Pubmed, Science Direct, Clinicalkey, and Scopus. Observational studies, case series, and individual case studies enrolling naïve-treatment and switch-therapy nAMD patients who received intravitreal injection of brolucizumab were eligible for this review. Result: We included 12 studies, comprising 772 patients and 848 eyes, that reported the outcome of intravitreal injection of brolucizumab in real-world practice. The mean age of patients was 77 years old. Follow-up period ranged from 7,2 weeks to 52 weeks. Improvement in visual acuity was mostly observed in treatment-naïve groups, ranging from +4,5 to +11,9 Early Treatment Diabetic Retinopathy Study (ETDRS) letters. Improvement in retinal thickness and reduction in retinal fluids were reported in both groups, with mean central retinal thickness (CRT) change of 94,92 μm. Significant reductions of subretinal fluid (SRF) were observed in 4 studies, intraretinal fluid (IRF) in 2 studies, and pigment epithelial detachment (PED) in 3 studies. Eight studies reported injection interval, the longest of which extended to 12 weeks. Inflammatory events following brolucizumab injection were reported in 8,01% of eyes, ranging from mild to severe inflammation, with 34,2% of the intraocular inflammation occurring in the vitreous (22 eyes). Brolucizumab may help alleviate treatment burden in real-world clinical setting by reducing disease activity, mainly demonstrated as improvement in retinal thickness, reduction in retinal fluid, and prolongation of injection interval. Clinicians must be aware of the possible inflammatory events following brolucizumab injection.